Tracking deaths of people who have experienced homelessness: a dynamic cohort study in an Australian city - Lisa Wood; Shannen Vallesi; Matthew Tuson (BMJ Open)
Objective Life expectancy and rates of premature death are fundamental markers of health and social equity globally, and measures on which people experiencing homelessness face enormous disparities. However, unlike for other population groups with similar disparities, concerted government action to reduce homeless mortality is rare, partly due to a lack of reliable, timely data. Contemporaneous tracking of homeless deaths is required to render such deaths less invisible and measure trends over time. Drawing on multiple data sources as recommended by the US National Health Care for the Homeless Council’s seminal Homeless Mortality Data Toolkit, we routinely and contemporaneously capture, verify and report on deaths occurring among people who have experienced homelessness in the Australian city of Perth.Design Dynamic cohort study.Setting Perth, Western Australia, Australia, between 2016 and 2022, with deaths examined between 2020 and 2022.Participants For this study, the cohort comprised 8753 people who experienced homelessness in Perth, with ‘recruitment’ into the cohort governed by engagement with one or more local homelessness services and programmes over the period.Outcome measures Number and median age-at-death statistics.Results There were 360 deaths over the 3-year period, which is likely an undercount. The median age at death was 50 years, >3 decades below the current Australian median age at death of 82 years. Aboriginal people accounted for 30% of the deaths.Conclusion The ongoing poor health and premature death of people who have experienced homeless are indictments on our society. Triangulation of multiple data sources is required to identify and monitor deaths among homeless populations. Timely, verified data on homeless mortality are important for galvanising action and accountability, and targets should be set to reduce the observed three-decade life expectancy chasm.